PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Suci Dua Mareta; Sawiji, Hery (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to determine: (1) the influence of leadership style on employee performance, (2) the influence of the work environment on employee performance, (3) the influence of leadership style experience and the work environment together on employee performance. This research is quantitative research using the correlational method. This method is suitable for testing variable hypotheses. The sampling technique was carried out using non-probability sampling with a saturated sampling method or total sampling. The sample used in this research was 30 employees of BALITBANGDA Surakarta City. Data collection was carried out using research questionnaires. The data analysis technique uses multiple linear regression analysis techniques. The research results show that: (1) there is a positive and significant influence of leadership style on employee performance (t = 23.67, sign 0.00), (2) there is a positive and significant influence of the work environment on employee performance (t = 28.6 , sign = 0.00), (3) there is a simultaneous influence of leadership style and work environment on employee performance (f = 1672.57, sign 0.00). The results of this research show that the effective contribution value or contribution size of the two independent variables, namely leadership style and work environment, to employee performance is 99%. Meanwhile, the remaining 1% (100% - 99%) is influenced by other factors not examined in this